Outcomes of Monochorionic, Diamniotic Twin Pregnancies with Prenatally Diagnosed Intertwin Weight Discordance - Sobhani, Nasim C.; Sparks, Teresa N.; Gosnell, Kristen A.; Rand, Larry; Gonzalez, Juan M.; Feldstein, Vickie A. (American Journal of Perinatology, 2020)
Objective Monochorionic, diamniotic (MCDA) twin pairs are predisposed to various pregnancy complications due to the unique placental angioarchitecture of monochorionicity. Few studies have evaluated the outcomes of weight-discordant MCDA pairs without selective fetal growth restriction (SFGR) or the risk factors for development of SFGR. This study aims to describe the natural history of expectant, noninvasive management of weight-discordant MCDA twins and to evaluate risk factors associated with progression to SFGR.Study Design This was a retrospective cohort study at a single, tertiary care center in the United States. All MCDA twins with isolated intertwin weight discordance (ITWD) ≥ 20% diagnosed before 26 weeks' gestational age (GA) were included. The primary outcome of descriptive analyses was overall pregnancy outcome, incorporating both survival to delivery and GA at delivery, as defined by the North American Fetal Therapy Network. The secondary outcome was SFGR in one twin (defined as estimated fetal weight < 10% for GA) and factors associated with this progression. Only those with fetal ultrasound (US) within 4 weeks of delivery were included in this secondary analysis.Results Among 73 MCDA pairs with ITWD, 73% had a good pregnancy outcome, with dual live delivery at a median GA of 33 weeks. Among the 34 pairs with adequate US follow-up, 56% developed SFGR. There were no differences in GA at delivery or discordance at birth between those who did and those who did not develop SFGR. There was a nonsignificant association between increasing ITWD at diagnosis and subsequent development of SFGR.Conclusion Expectant, noninvasive management can be considered in MCDA twin pregnancies with ITWD ≥ 20% diagnosed before 26 weeks. This approach is associated with a good pregnancy outcome in the majority of cases, even after the development of SFGR in the smaller twin.Key Points
Keywords: monochorionic; unequal placental sharing; growth discordance; discordant MCDA twins